2022
DOI: 10.1002/ajb2.16070
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation of seed and seedling traits along a natural aridity gradient may both predict and constrain adaptive responses to climate change

Abstract: Premise: Variation in seed and seedling traits underlies how plants interact with their environment during establishment, a crucial life history stage. We quantified geneticbased variation in seed and seedling traits in populations of the annual plant Plantago patagonica across a natural aridity gradient, leveraging natural intraspecific variation to predict how populations might evolve in response to increasing aridity associated with climate change in the Southwestern U.S. Methods: We quantified seed size, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…Previous work in contemporary populations of P. patagonica has shown that seedlings with larger leaves survive terminal drought for longer than those with smaller leaves (Christie et al, 2022). Descendant populations of P. patagonica have shifted their resource allocation strategies towards greater vegetative investment at the cost of fecundity (Figure 3), as such a strategy may prioritize survival under increasingly arid conditions associated with prolonged drought in the region.…”
Section: Drought Resilience Via Altered Life History Strategiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work in contemporary populations of P. patagonica has shown that seedlings with larger leaves survive terminal drought for longer than those with smaller leaves (Christie et al, 2022). Descendant populations of P. patagonica have shifted their resource allocation strategies towards greater vegetative investment at the cost of fecundity (Figure 3), as such a strategy may prioritize survival under increasingly arid conditions associated with prolonged drought in the region.…”
Section: Drought Resilience Via Altered Life History Strategiesmentioning
confidence: 98%
“…The species is an obligate inbreeder with cleistogamous flowers (Sharma et al, 1992). Among populations from the Colorado Plateau, seed and seedling traits show evidence of local adaptation across a natural aridity gradient (Christie et al, 2022), suggesting that abiotic selection has shaped trait variation.…”
Section: Study System and Seed Samplingmentioning
confidence: 99%
“…The hypothesis tested in this experiment was that the seed coat is impermeable to water, and a puncture on the seed coat will allow for water uptake without resistance. Castor seeds were incubated to germinate at temperatures of 16,19,22,25,28,31, and 34 °C. For each temperature, 70 castor seeds of the cultivar AKB 02 had the caruncle manually removed, and a small puncture was made in 35 seeds.…”
Section: Imbibition and Germination Influenced By Temperature And A P...mentioning
confidence: 99%
“…Many studies on other plant species have demonstrated the weak association between seed size and the time for germination and seedling emergence [31,32]. Corn (Zea mays) producers blame the variability in seed size for uneven seedling emergence [50]; however, while the effect of seed size is occasionally observed in the laboratory, it is not confirmed in field conditions.…”
Section: Morphological Traits Have Small Influence On the Time For Ge...mentioning
confidence: 99%
See 1 more Smart Citation